2017
DOI: 10.1016/j.cellsig.2017.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic triple-negative breast cancer is dependent on SphKs/S1P signaling for growth and survival

Abstract: About 40,000 American women die from metastatic breast cancer each year despite advancements in treatment. Approximately, 15% of breast cancers are triple-negative for estrogen receptor, progesterone receptor, and HER2. Triple-negative cancer is characterized by more aggressive, harder to treat with conventional approaches and having a greater possibility of recurrence. Sphingosine-1-phosphate (S1P) is a bioactive sphingolipid signaling mediator has emerged as a key regulatory molecule in breast cancer progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 54 publications
5
61
0
1
Order By: Relevance
“…Sphingosine kinase 2 expression has been found elevated in both colon cancer and non‐small cell lung cancer (NSCLC) . In NSCLC tumor tissues, high expression of SphK2 has been associated with cancer progression and has served as an independent prognostic factor for OS and disease‐free survival (DFS), supporting the idea of endogenous SphK2 as a potential cancer‐promoting factor in other human cancers, including breast . To determine the importance of SphK2 in breast cancer clinical tissue samples, we used TCGA, one of the two large breast cancer patient cohorts for gene expression data analysis, and found SphK2 transcripts were significantly elevated in breast cancer patients compared to matched controls (Figure A, left).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sphingosine kinase 2 expression has been found elevated in both colon cancer and non‐small cell lung cancer (NSCLC) . In NSCLC tumor tissues, high expression of SphK2 has been associated with cancer progression and has served as an independent prognostic factor for OS and disease‐free survival (DFS), supporting the idea of endogenous SphK2 as a potential cancer‐promoting factor in other human cancers, including breast . To determine the importance of SphK2 in breast cancer clinical tissue samples, we used TCGA, one of the two large breast cancer patient cohorts for gene expression data analysis, and found SphK2 transcripts were significantly elevated in breast cancer patients compared to matched controls (Figure A, left).…”
Section: Resultsmentioning
confidence: 99%
“…Human LM2‐4 cells, obtained from Dr John Ebos, Roswell Park Comprehensive Cancer Center (RPCCC), are a metastatic variant of the triple‐negative MDA‐MB‐231 breast cancer cell line derived after multiple rounds of in vivo lung metastasis selection in mice, and were grown as previously described . LM2‐4 and MDA‐MB‐231 cells were maintained in phenol‐red free RPMI (Gibco BRL, Grand Island, NY, USA) media containing 10% of heat‐inactivated Fetal Bovine Serum (FBS), 100 μg/mL of penicillin, and 100 μg/mL of streptomycin (Gibco) as described previously . Low passage cells (<10 passages) were used for all experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that while 66.1 cells implanted and sealed into the bone do not metastasize within the 14-day test period in the absence of fracture [32] and are not likely to contribute directly to increased S1P in the spinal cord, local increases in S1P in the tumor-bearing bone could sensitize peripheral afferents [11; 30; 46] and promote the development of CIBP and spinal S1P production by provoking adaptive glutamatergic and neuroinflammatory changes in the spinal cord [51]. S1P has emerged as a key regulatory molecule in breast cancer [22; 37; 49] and thus, reduction of its levels by FTY720 and/or altering S1P signaling may reduce breast cancer growth and bone metastasis and may partially be responsible for the decrease in CIBP, supporting its clinical use in metastatic cancers.…”
Section: Discussionmentioning
confidence: 99%
“…We have established methods to measure the levels of S1P in tumor interstitial fluid (11) and lymphatic fluid (12), and demonstrated that S1P is associated with lymphangiogenesis and lymph node metastasis both in an animal model (13, 14) and in patients (15), which suggests that S1P in the tumor microenvironment worsens cancer progression (9, 13, 1618). Furthermore, we recently found that S1P signaling plays an even more important role in metastatic triple-negative breast cancers (19). Given that S1P signaling is related to cancer malignant potential and progression, we hypothesized that S1P may contribute to doxorubicin resistance.…”
Section: Introductionmentioning
confidence: 99%